METHODOLOGY OF SAMPLING, FIELD AND LABORATORY TESTING TO DETERMINE THE GEOTECHNICAL PROPERTIES OF SOILS COMMON IN THE FERGANA REGION - Khakimova Kamola Rakhimjonovna; Imomaliyeva Zarnigor Oybek kizi (Modern American Journals, 2025)
The article proposes a comprehensive methodology based on sampling, field and laboratory tests to determine the geotechnical properties of soils widespread in the Fergana region. Initially, the geological-geotechnical and seismic conditions of the area, the characteristics of irrigated and saline soils are analyzed, and the limitations of traditional approaches are shown. The proposed methodology is developed in the spirit of the requirements of Eurocode 7 and ISO 17892 and involves the integrated use of drilling, SPT/CPT soundings, disturbed and undisturbed sampling, and laboratory physical, compaction, consolidation, triaxial and straight-cut tests. By determining salinity and chemical composition (water-soluble salts, pH, trace elements), the ability to assess the structural stability and long-term deformation processes of soils is expanded. Local empirical connections between the results of field surveys and laboratory indicators were formed, and an approach to determining characteristic and calculated values based on statistical analysis of geotechnical parameters was established. As a result, an excellent field-laboratory methodology was developed that fully reflects the real geotechnical behavior of soils in the conditions of the Fergana region, serves to reduce seismogeotechnical risks and reliably predict the settlement and stability of foundations.
Keywords: Fergana region, geotechnical properties of soils, sampling, field tests, SPT, CPT, laboratory tests, consolidation, Eurocode 7, salinity, seismogeotechnical model.